PENGARUH INSENTIF TERHADAP SEMANGAT KERJA KARYAWAN PADA PT. SARI LEMBAH SUBUR DI KECAMATAN GANDUANG KABUPATEN PELALAWAN - Hasdian Saputra; Lena Farida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to identify and analyze incentives and employee morale at PT. Sari Lembah Subur Sub-District. Ganduang District Pelalawan as well as to determine the influence of Incentives Against Employee Morale on the PT. Sari Lembah Subur Sub-District. Ganduang District Pelalawan. Providing incentives for production employees at PT. Sari Lembah Subur Sub-District. Ganduang District Pelalawan already well underway. However, there are deficiencies which led incentives granted to employees perceived by respondents still inadequate. As well as employee morale in the production of PT. Sari Lembah Subur Sub-District. Ganduang District Pelalawan already good. However, there are deficiencies that cause not maximum employee morale. Results of analysis with SPSS, showed that the independent variables are incentives (X) has a very strong relationship to the dependent variable, namely Employee Morale (Y). Incentives provide a positive and significant influence on Employee Morale, so if it will lead to enhanced incentives to increase employee morale.